Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10531-004-5020-2
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness and Habitat Use of Small Carnivores in the Arusha National Park (Tanzania)

Abstract: The carnivore community of Arusha National Park, Tanzania, was monitored using live trapping and diurnal and nocturnal visual counts and recording of tracks and signs along line transects. Nine carnivore species were recorded. Hyena (Crocuta crocuta), the most common large species, leopard (Panthera pardus) and African civet (Civettictis civetta) were detected along line transects, while the smaller species were counted and/or captured. Mungos mungo, Galerella sanguinea, and Genetta maculata were the most prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Most of the herpestid woodland encounters were of dwarf mongooses that use large termite mounds as dens and/or food sources, while bushy-tailed mongooses account for most of the forest encounters. These patterns of habitat use of Issa herpestids are consistent with those of herpestids at other sites (Caro and Stoner 2003;Martinoli et al 2006;Waser et al 1995). Leopards and hyenas were the two most frequently encountered carnivores during this study (leopards directly and hyenas indirectly), which likely account for the habitat use patterns found for carnivores; leopards are found in a variety of habitats, but prefer those with dense vegetation (i.e., forest or closed woodland), while hyenas tend to prefer open grassland (Durant et al 2010;Estes 1991;Kingdon 1997;Pettorelli et al 2010).…”
Section: Other Faunasupporting
confidence: 79%
See 1 more Smart Citation
“…Most of the herpestid woodland encounters were of dwarf mongooses that use large termite mounds as dens and/or food sources, while bushy-tailed mongooses account for most of the forest encounters. These patterns of habitat use of Issa herpestids are consistent with those of herpestids at other sites (Caro and Stoner 2003;Martinoli et al 2006;Waser et al 1995). Leopards and hyenas were the two most frequently encountered carnivores during this study (leopards directly and hyenas indirectly), which likely account for the habitat use patterns found for carnivores; leopards are found in a variety of habitats, but prefer those with dense vegetation (i.e., forest or closed woodland), while hyenas tend to prefer open grassland (Durant et al 2010;Estes 1991;Kingdon 1997;Pettorelli et al 2010).…”
Section: Other Faunasupporting
confidence: 79%
“…Most of the encounters in the "other" category were of elephant shrews foraging in the leaf litter of forest floors, so it is not surprising that forest was used significantly more than woodland. The use of more open woodland habitat is reflective of the encounters of hyraxes and hares, while other animals, such as genets and pangolins, were most often seen in forest, as would be expected based on their general habitat preferences at other sites (Estes 1991;Kingdon 1997;Martinoli et al 2006;Skinner and Chimimba 2005). Finally, the disparity in habitat use by rodents can be explained by the large number of encounters of squirrels and porcupines, animals that more often use woodland habitats as compared to forest (Corbet and Aarde 1996;Emmons 1980;Estes 1991;Kingdon 1997de Villiers and van Aarde 1994).…”
Section: Other Faunamentioning
confidence: 95%
“…Despite the importance of small-and medium-sized carnivores for ecosystem dynamics, particularly in African savanna rangelands, research, status, and management activities have gained little attention (Martinoli et al 2006). Although small-and medium-sized carnivores are often still abundant in arid savanna rangelands, recent studies in the southern Kalahari found that small carnivores are locally declining, caused by grazing-induced changes in landscape structure (Blaum et al 2007a, c, d ).…”
mentioning
confidence: 99%
“…Newmark, 1996;Stephens et al, 2001), (iii) establishing species inventories (e.g. Martinoli et al, 2006) and (iv) analysing the general state (e.g. habitat quality, fragmentation) of the protected area (e.g.…”
Section: Introductionmentioning
confidence: 99%